2018
DOI: 10.4014/jmb.1802.10001
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Carbohydrate-Binding Module (CBM) of an Endo-��-1,4-glucanase (Cel5L) from Bacillus sp. KD1014 in Thermostability and Small-Substrate Hydrolyzing Activity

Abstract: An endo-β-1,4-glucanase gene, cel5L, was cloned using the shotgun method from Bacillus sp.. The gene, which contained a predicted signal peptide, encoded a protein of 496 amino acid residues, and the molecular mass of the mature Cel5L was estimated to be 51.8 kDa. Cel5L contained a catalytic domain of glycoside hydrolase (GH) family and a carbohydrate-binding module family 3 (CBM_3). Chromatography using HiTrap Q and CHT-II resulted in the isolation of two truncated forms corresponding to 50 (Cel5L-p50) and 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…brachycerastes and a cellobiohydrolase from C. thermocellum (Xyl-ORF19). , These facts reinforce the role of the Big_2 domain in the enhancement of thermostability, which is consistent with the observations from some CBMs. , …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…brachycerastes and a cellobiohydrolase from C. thermocellum (Xyl-ORF19). , These facts reinforce the role of the Big_2 domain in the enhancement of thermostability, which is consistent with the observations from some CBMs. , …”
Section: Resultssupporting
confidence: 80%
“…17,24 These facts reinforce the role of the Big_2 domain in the enhancement of thermostability, which is consistent with the observations from some CBMs. 36,37 To date, CBMs have been extensively applied to construct functional fusion proteins with an enhanced catalytic activity, carbohydrate-binding activity, and stability. 38,39 In this study, similar to some unique properties of CBMs, PpBig_2 was demonstrated to play an essential role in the kinetic parameters (Table 1), κ-carrageenan-binding capability, mode of action, and thermostability of PpCgk.…”
Section: Resultssupporting
confidence: 54%
“…In the same way, studies of the role of CMB3 of Bacillus sp. KD1014 suggest that it contribute in thermostability, and affinity and substrate specificity for small substrates (Lee et al 2018).…”
Section: About Xylanase Activity Thermostablementioning
confidence: 99%